Issues of Regulation of Land Relations in Uzbekistan Study the Correlation between Anti - Mullerian Hormone and some trace elements (selenium, copper, zinc, and iron) in infertile women: A review - Inam Joudah Radhi; Hameedah Hadi Abdulwahid; Zena T Omran (Zien Journals, 2023)
A clinical pregnancy cannot be achieved until at least 12 months have passed after the last unprotected, routine sexual activity. It usually has an impact on the reproductive system and is referred to as infertility. Infertility rates have increased in recent years. Cell differentiation and development are significantly influenced by the glycoprotein known as anti-Müllerian hormone, which is produced by the granulosa cells of preantral and microantral follicles. Cell differentiation and development are significantly influenced by the glycoprotein known as anti-Müllerian hormone, which is produced by the granulosa cells of preantral and microantral follicles. It affects the regulation of folliculogenesis. For the preservation of human health and the prevention of several health problems, trace elements are crucial. Numerous disorders are brought on by changes in the natural balance of trace elements, and biological systems may also be adversely affected. This study looked at the potential importance of abnormalities in selenium, copper, zinc, and iron levels as well as anti-Mullerian hormone levels in infertile women
Keywords: Infertility disease; AMH; Trace elements